Recommendations for fertility preservation in patients with lymphoma, leukemia, and breast cancer - Kim, S. Samuel (Springer US, 2012)
Fertility issues should be addressed to all patients in reproductive age before cancer treatment. In men, cryopreservation of sperm should be offered to all cancer patients in reproductive age regardless of the risk of gonadal failure. In women, the recommendation of fertility preservation should be individualized based on multiple factors such as the urgency of treatment, the age of the patient, the marital status, the regimen and dosage of cancer treatment.